O Populismo nas eleições de 1989: a constituição do povo nos discursos de Collor e Lula - Benites, Luis Eduardo Sandim (2012)
The framing of this study on the 1989 presidential elections was focused on the ideological speech construction of the candidates, Fernando Collor de Mello and Luiz Inácio Lula da Silva during the campaigning period between the first and the second election polis. The research was conducted after the observation of the pre-election political programs exhibited during the carge-free TV prime-time political features, which material was obtained from the DOXA IUPERJ (The Institute and its Communication Laboratory), a department of the UCAM/RJ (Universidade Cândido Mendes Rio de Janeiro). Some documents on the proposais presented by candidates. Which were located in the Getúlio Vargas Foundation (CP.DOC/FGV) Research and Documentation Center archives were also investigated. Some additionar data was obtained from copies of the veja magazine issues of that period and also from the historical literature pertaining to the José Sarney presidential administration. Then we tried to cast out the status quo condition during which both ideological discourses emerged. The analysis of discourse categories elaborated within the context of Ernesto Laclau's, Chantal Mouffe's, and their follower' also served as an instrument for the appropriation of the researched political events that shone upon that period. Among the discourse analysis elements operated along this study, the antagonism and the logical differences and equivalences can be mentioned, i. e., those mechanisms that allow for the verification on how the candidates respective ideological speecheswere constructed along that timeline. A few academic papers on populism that helped us in the role of mentors to straighten our own research approach perspective can also be pinpointed. Paramount among these was the categorization of the concept, people , as its construction makes up for essential data on the articulation of the demands concept, in the sense of constitutive elements of a social environment that may influence the build-up of a political discourse whenever jointly worked upon